Analisis Pengukuran Kinerja PT telekomunikasi Indonesia Tbk Periode Tahun 2013 - 2016 - supratman 19 63 (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT PERFORMANCE MEASUREMENT ANALYSISPT TELEKOMUNIKASI INDONESIA TbkPERIOD YEAR 2013 – 2016 The purpose of this study to prove the extent of performance degradation at PT. Telekomunikasi Indonesia and analyzed the economic value-added to determine the company's actual financial condition.The research method used is descriptive research in case study and library research and using quantitative analysis method approach. The data used in this study is secondary data include financial statements, stock price index and interest rates obtained through literature study. The data are analyzed to estimate the rate of capital cost of the loan, the level of own capital cost and the WACC used to calculate EVA. Further testing of the period of 2013 to 2016 period is done with both ROI and EVA performance measurements.The study also takes into account the fluctuations in the rate of borrowing cost of capital and the very high level of own capital costs. This attention to the composition of capital resulted in the high cost of capital to be borne by the company thus reducing the ability to create value that is not a value added for both the company and consumers also help create economic value-added.